A Case of Persistent Generalized Retrograde Autobiographical Amnesia Subsequent to the Great East Japan Earthquake in 2011 - Yuji Odagaki (Case Reports in Psychiatry)
Functional retrograde autobiographical amnesia is often associated with physical and/or psychological trauma. On 11 March 2011, the largest earthquake on record in Japan took place, and subsequent huge tsunami devastated the Pacific coast of northern Japan. This case report describes a patient suffering from retrograde episodic-autobiographical amnesia for whole life, persisting for even more than five years after the disaster. A Japanese man, presumably in his 40s, got police protection in April 2016 but was unable to respond to question about his own name. He lost all information about his personal identity, and his memory was wholly lost until the disaster on 11 March 2011. He was able to recall his life after the disaster, and semantic memories and social abilities were largely preserved. A medical examination performed on 1 November 2016 verified that he was awake, alert, and oriented to time, place, and person (except for himself). General physical and neurological examinations revealed no pathological findings. He also experienced some symptoms associated with posttraumatic stress disorder (PTSD), such as intrusive thoughts, flashbacks, and nightmares. No abnormalities were detected by biochemical test and brain magnetic resonance imaging (MRI). Physicians and other professionals who take care of victims of disaster should be aware of dissociative spectrum disorders, such as psychogenic amnesia.